2014
DOI: 10.1179/1607845414y.0000000180
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein-associated phospholipase A2 (Lp-PLA2) and tumor necrosis factor-alpha (TNF-α) and their relation to premature atherosclerosis in β-thalassemia children

Abstract: Premature atherosclerosis is common among young thalassemia children. Lp-PLA2 and TNF-α are significantly increased in thalassemia children and show strong correlations with cIMT, suggesting that both of them may be appreciated as modulating factors in carotid atherosclerosis pathophysiological process among these children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Previous studies have shown that some cytokines(such as TNF-α, IL-1,8,12 and IFN-γ etc.) promote the occurrence of atherosclerosis 44 - 65 , while others(such as TNF-β, IL-4 and IL-10 etc.) inhibit the process of atherosclerosis 1 , 61 , 66 - 75 (see Table 1 ).…”
Section: Thymus Can Directly or Indirectly Modulate Inflammatory Procmentioning
confidence: 99%
“…Previous studies have shown that some cytokines(such as TNF-α, IL-1,8,12 and IFN-γ etc.) promote the occurrence of atherosclerosis 44 - 65 , while others(such as TNF-β, IL-4 and IL-10 etc.) inhibit the process of atherosclerosis 1 , 61 , 66 - 75 (see Table 1 ).…”
Section: Thymus Can Directly or Indirectly Modulate Inflammatory Procmentioning
confidence: 99%
“…Among the pro-inflammatory cytokines, multiple studies have focused on TNF-α being an endogenous pyrogen, which can cause inflammation, apoptotic cell death, and mediate the release of variety cytokines like IL-6, IL-8 and IL-1β by stimulated macrophages [ 16 , 17 ]. Dysregulation, especially overproduction of TNF-α, has been found in a variety of human diseases including atherosclerosis [ 18 ], cancer [ 19 ], atherosclerosis [ 20 ] and inflammatory bowel disease [ 21 ]. However, it is still unclear, and many studies of depression are currently being connected to the TNF-α level.…”
Section: Introductionmentioning
confidence: 99%
“…Lipoprotein-associated phospholipase A2 (Lp-PLA2) is excreted predominantly from atherosclerotic plaques by macrophages and neutrophils and subsequently circulates in the blood stream ( 10 ). It has been demonstrated that Lp-PLA2 is a potentially important pathogenic factor participating in the progression of atherosclerosis ( 11 ). In an animal model of hyperlipidemia and hyperglycemia, an Lp-PLA2 inhibitor reduced macrophage accumulation, and diminished the necrotic lipid-core volume and fibrous cap of coronary atherosclerotic plaques ( 12 ).…”
Section: Introductionmentioning
confidence: 99%